Structural Fire Engineering - Kodur, Venkatesh K.R; Naser, M.Z (McGraw-Hill's AccessEngineering., 2020)
"This hands-on guide clearly explains the complicated building codes and standards that relate to fire design. The book presents actionable strategies that engineers can apply to help prevent or mitigate the effects of fire in structures. Written by a pair of internationally recognized experts, Structural Fire Engineering covers all of the current fire design requirements of the IBC, IFC, NFPA Fire Code, and National Building Code of Canada. You will get step-by-step instruction on performing fire resistance evaluation using both testing and calculation methods."--Publisher's description.